Seasonal variations of rosmarinic and carnosic acids in rosemary extracts. Analysis of their in vitro antiradical activity - Luis, J.C.=700 1 Johnson, C.B.
(Es, En)
ilus., 18 ref.
Keywords: ROMERO; COMPOSICION QUIMICA; ACIDOS FENOLICOS; ANTIOXIDANTES; DITERPENOS; ESPAÑA